The Role of the Conformation of Holstein Cows in the Sustainability of Milk Production - Zsolt J. Korösi; László Bognár; Szabolcs Bene; Ferenc Szabó (Chemical Engineering Transactions)
The conformation of dairy cows, referring to their physical form and the arrangement of body parts, plays a critical role not only physiologically but also economically. It is intricately linked to key sustainability traits such as milk production, reproduction, and longevity. Research has revealed genetic correlations between body conformation traits and first lactation milk yield ranging from 0.48 to 0.54, and correlations between fertility and type traits vary from zero to 0.79. The relationships between productive life or herd life and type traits range from –0.06 to 0.16, with negative correlations observed for characteristics such as rump angle, rear leg set, udder depth, and teat length. Larger cows with slightly positive conformation traits are associated with longer herd life. Specifically, cows with well-attached fore udders, high rear udder attachment, strong central ligaments, close front teat placement, and moderately long teats are linked to the longest functional, productive lives. The heritability estimates for conformation traits are moderate, ranging from 0.20 ± 0.047 to 0.38 ± 0.04. These correlations and heritability values highlight the need for breeders to reassess and prioritise conformation traits within Holstein dairy cow breeding programs. By revising the traits scored and incorporating new ones during selection, breeders can indirectly improve milk production, reproduction, and longevity, enhancing the sustainability of milk production. This review paper aims to summarise current official type evaluation systems for Holstein cows, underscore the significance of various conformation traits in sustainable milk production, and propose potential enhancements to the scoring system.